精益六西格玛管理在急性缺血性脑卒中患者 急救护理流程优化中的应用. - 左霞; 孙四平; 赵霞 (Nursing of Integrated Traditional Chinese & Western Medicine, 2019)
Objective To investigate the effect of Lean Six Sigma (LSS) in process optimization of emergency care of patients with acute ischemic stroke (AIS). Methods Totally 62 AIS patients with hospital admission between October 2017 and October 2018 were included as the control group, another 64 patients with hospital admission between November 2018 and May 2019 were included as the observation group. The routine process management of emergency care was adopted in the control group, and a LSS project was used in process optimization of emergency care in the observation group. The time to reception, time of CT-scanning completion, specimen delivery and laboratory test were observed and compared between two groups. Results The time to reception, time of CT-scanning completion, time of specimen delivery and time of laboratory test in the observation group were lower than those in the control group (P <0. 01). Conclusion The LSS project is an effective tool in process optimization of emergency care of AIS patients.